Knowledge, attitude and practice regarding breastfeeding among COVID-19 positive mothers delivered in a tertiary care centre - Shyamala, A.; Subasakthi, A.; Suresh, P. M. (International Journal of Contemporary Pediatrics, 2022)
Background: WHO recommends exclusive breastfeeding in COVID-19 mothers. Colostrums not only provides the optimum source of nutrients for the neonate and its first strong protection against infection. Breast feeding lays the foundation for psychological bonding between the baby and the mother. This study assessed breastfeeding knowledge, attitudes, and practices among COVID-19 mothers. Methods: In this cross-sectional study sixty-three COVID-19 positive mothers who delivered in Kanyakumari Government Medical College and had at least one child aged 2 years or younger were evaluated with an online self-reported knowledge, attitude, and practice questionnaire regarding breastfeeding. The purpose of the study was explained and informed consent was obtained on voluntary basis. The data collected was entered into Microsoft excel, analysed using SPSS version 23.0, using descriptive statistics comprising of frequencies, percentages and, measures of central tendencies. Results: 74.6% of mothers had good knowledge,63.4% displayed good attitude and 58.7% had good breastfeeding practices. A total of 65.1% of the mothers know the importance of exclusive breastfeeding and 46% gave breastmilk as the first feed. Conclusions: Breastfeeding knowledge was good among COVID-19 mothers, breastfeeding practice was suboptimal. Mothers should be counselled that the benefits of breastfeeding outweigh the risks for transmission.